GENDER REASSIGNMENT AND THE WORLD OF WORK: A COMPARATIVE PERSPECTIVE ON THE INTERSECTION BETWEEN TRANSGENDERISM, TRANS- SEXUALITY AND APPEARANCE DISCRIMINATION IN THE SOUTH AFRICAN EMPLOYMENT ARENA - DM Smit; D Viviers (Obiter, 2016)
The media hype in 2015 surrounding the former Olympic athlete Bruce Jenner’s gender transition to become “Caitlyn” has put renewed focus on the issue of trans-individuals and gender reassignment. Unlike Caitlyn, however, many transsexual individuals need to function within and face an office environment every day, where employers and co-workers are not necessarily accommodating or tolerant. Workplace discrimination against transsexual employees, based on their altering or altered appearance due to gender reassignment, is a prevalent concern in places of employment across the globe, and South Africa is no exception. Employers and co-workers’ subconscious appearance preferences seem to filter into employment decisions, policies and practices, causing trans-employees to suffer severe prejudice. Against the backdrop of case law and legislative developments in foreign jurisdictions as well as locally, this article assesses the formal protection afforded to trans-employees in South African workplaces. It is argued that, apart from the existing protection against sex-based and gender-based unfair discrimination, trans-employees should also be explicitly afforded formal protection against unfair discrimination on the ground of appearance before, during and after gender reassignment. The study concludes with concrete proposals to remedy the situation and contributes to a more tolerant and effective employment realm, irrespective of appearance.